Comparative phylogenetic analysis of complete plastid genomes of Renanthera (Orchidaceae) - Xiao, Tao; He, Liefen; Yue, Liangliang; Zhang, Yonghong; Lee, Shiou Yih (Frontiers in Genetics, 2022)
Owing to its attractive flower shape and color, Renanthera (Orchidaceae), comprising about 19 species, has significant ornamental value as a houseplant, in floral design and in landscape gardens. Two species of Renanthera are categorized as endangered and critically endangered in China’s Red List and international trade in these orchids is currently strictly monitored by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). This paper reports on the de novo assembled and annotated plastome of four species of Renanthera; R. citrina, R. coccinea, R. imschootiana, and R. philippinensis. The length of the plastome sequences ranged from 144,673 bp (R. imschootiana) to 149,007 bp (R. coccinea) with GC content of 36.6-36.7%. The plastomes showed a typical quadripartite structure, including a large single-copy (84,241—86,404 bp), a small single-copy (11,468—12,167 bp), and a pair of inverted repeats (24,482—25,715 bp) regions. Of the 120 genes detected, 74 were protein coding, 38 were tRNA, and eight were rRNA genes. The plastome of Renanthera is rather conserved, but nucleotide variations that could distinguish them apart are noticeable – the total number of tandem repeats ranged from 62 (in R. imschootiana) to 74 (in R. citrina); while the number of long repeats ranged from 21 (in R. imschootiana and R. philippinensis) to 43 (in R. citrina). Three hypervariable regions (psbI-trnS-GCU, trnG-GCC, rpl32) were identified. Phylogenetic analyses based on the CDS using maximum likelihood (ML) and Bayesian inference (BI) revealed that Renanthera is closely related to Holcoglossum, Neofinetia, Pendulorchis, and Vanda. The relationship between the four species of Renanthera was fully resolved; a monophyletic clade was formed and R. coccinea was recorded as the first to diverge from the rest. The genetic data obtained from this study could serve as a useful resource for species identification in Renanthera as well as contribute to future research on the phylogenomics of Orchidaceae.